Intraspecific Genetic Variation of Five Wild Indonesian Striped Snakehead (Channa striata (Bloch, 1793)) Populations Assessed Through 16S rRNA Sequences - Suryani, Tuty Ari; Hastiwi, Titik Tri; Fitriani, Shentarya; Agiestina, Putri; Fajar, Ibnu; Aji, Katon Waskito (Indonesian Fisheries Research Journal, 2023)
The striped snakehead (Channa striata) belongs to the order Perciformes, suborder Channoidei, and the family Channidae. This fish is native to Sumatra, Java, and Kalimantan, but introduced to Sulawesi and Papua. Channa striata have potential as a food source, and pharmacological agent. However, the study on the genetic variation of snakehead fish in Indonesia is currently limited to specific areas, thus the genetic data obtained is insufficient. Therefore, the aim of this study was to examine the intraspecific genetic variation of the striped snakehead from five different locations in Indonesia using the 16S mitochondrial gene as a genetic marker. The PCR method was conducted with two primers, 16Sar and 16Sbr. The data obtained were then analyzed using DNASTAR, BLAST, Mesquite, MEGAX, BEAST, DnaSP, and NETWORK. The result revealed that all striped snakeheads investigated have 98.85-99.51% similarity to C. striata from the GenBank. The mtDNA 16S sequences generated 5 haplotypes with 5 variable sites and 4 parsimony informative sites. The mean of haplotype diversity and nucleotide diversity were 0.706 ± 0.088 and 0.00325 ± 0.00052 respectively with genetic divergence ranging from 0% to 0.73%. The phylogenetic tree revealed two distinct clades which were supported by a bootstrap value of 100% (NJ and ML), as well as a posterior probability value of 1.00 (BI). This finding suggests that there is intraspecific genetic variation of wild striped snakehead populations in Indonesia, with two distinct groups consisting of the western part of Indonesia (Sumatera) and the central to the eastern part of Indonesia (Kalimantan, West Nusa Tenggara, and Papua). This study will be helpful in efforts to conserve and cultivate the striped snakehead through breeding programs in Indonesia.